Neonatal Outcomes and Frequency of Ultrasound in Pregnant Women With Prior Bariatric Surgery [26O]. (May 2020) - Wlodarczyk, Katarzyna; Harrison, Rachel; Allen, Katherine; Semons-Booker, Kia; Braun, Emilie; Cruz, Meredith
Abstract : INTRODUCTION: Infants of women who have undergone bariatric surgery are more likely to be born small for gestational age (SGA). We sought to identify whether increased ultrasound surveillance lead to better neonatal outcomes. We hypothesized that women with less than 2 ultrasounds (US) after their anatomical survey were more likely to have poor neonatal outcomes. METHODS: IRB approval was obtained. This was a single center, retrospective cohort study of 189 singleton pregnancies after bariatric surgery between 2005–2019. Patients were placed in 2 categories: those with less than 2 ultrasounds after fetal anatomic survey (FAS) or those with greater than or equal to 2 ultrasounds after FAS. US information and neonatal outcomes were compared between these two groups. A neonatal composite was utilized as a measure of adverse neonatal outcome. RESULTS: Of the 189 patients, 165 had documentation of FAS or beyond. 48 patients had less than 2 US and 117 had greater than or equal to 2 US. Women with less than 2 US had their last US at approximately 26.7 weeks (vs 36.5, P <.001), they were more likely to deliver at an earlier gestational age (36.6 vs. 38.2 weeks, P =.005), and had an increased likelihood of a composite adverse neonatal outcome (aOR 0.36, 95%CI 0.15–0.86) including NICU admission, jaundice, hypoglycemia, respiratory distress, and macrosomia, after controlling for confounders. CONCLUSION: Less frequent ultrasound surveillance in women with previous bariatric surgery is associated with earlier gestational age at delivery and higher rates of adverse neonatal outcomes.